The church's response to the HIV/AIDS epidemic in India - Nalini Arles (Acta Theologica)
I gratefully remember working with Reverend Charles in a rehabilitation centre in the US and later with my HIV-positive friends in India. Their laughter, courage and resilience reminded me that it is not they who are HIV-positive but it is we who are all HIV-positive. In this article I would like to reflect on the cultural context of HIV/AIDS in India, its prevalence and the Church’s response to this epidemic.